PENYEBAB KEJATUHAN HOSNI MUBARAK DAN PROSPEK DEMOKRATISASI DI MESIR - , Nuril Khasyiin Ardiansyah; , Dr. Eric Hiariej, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study discusses fall of the Mubarak regime by looking the factors and analyze how the authoritarian regime change toward democracy. January 25, became a real effort to realize that dream. This study begins with a discussion